PEMBERIAN BEBERAPA JENIS PUPUK ORGANIK DAN KEUNTUNGAN EKONOMI PADA BUDIDAYA PADI SAWAH DI KABUPATEN PIDIE - Helmi Helmi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2019)
The objectives of this study is to analysis the affectivities and rate of efficiencies of using organic fertilizer in rice cultivation. The research treatment was implemented atlowland rice ofMali Guyui village, Subdistrict of Sakti, Pidie District Province of Aceh. Study started in May to September 2018 had executed at irrigation rice field farm property of farmer with the treatment formation: (1) Manure, (2) Straw compost and (3) Treatment of farmer. The result of study showed that the highest grain yield was obtained at higher straw compost treatment of 800 kg/ha (11.11%) compared with the pattern of the farmers, and 640 kg/ha (8.69%) compared with manure treatment. The result of economic analysis showed that the level of benefits obtained by treatment of hay is higher IDR 580,600,- (7.42%) compared with the treatment of farmers with their conventional manures and the application of hay also bring the higher benefits IDR 1,582,480,- (23.19%) compared with chemical manure treatment. Key words :Rice, organic fertilizer, economic benefit